GAMBARAN BAKTERI Eschericia coli PADA CINCAU HITAM DENGAN METODE MPN DI PASAR KOTA MALANG - Hadiatun, Nurul; Anisa, Yufi Yuni; Hijriani, Baiq Isti (JSN : Jurnal Sains Natural, 2023)
Black cincau is a food that is consumed by many people. Black cincau is used as a mixture of drinks and facilitates the digestive system. Black cincau is widely traded in traditional markets, but the processing and presentation of blackcincau often ignores cleanliness or is unhygienic. Some are sold without special packaging and placed in open containers. Such conditions allow black cincau to be contaminated by dust and bacteria. Bacteria that often contaminate food are Coliform bacteria such as Escherichia coli. Some of the diseases caused by E. coli include; diarrhea, urinary tract infection, sepsis, and meningitis. The aim of this study was to describe the E. coli bacteria contaminating black cincau in the Malang city market. This type of research uses a descriptive method, namely identifying Escherichia coli bacteria by means of the MPN test. The results showed that there were two out of a total of five positive samples containing E.coli bacteria. The presence of E.coli bacteria in positive samples was indicated by the presence of metallic green colonies on EMBA media